2016
DOI: 10.1016/j.ibror.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

BDNF trafficking and signaling impairment during early neurodegeneration is prevented by moderate physical activity

Abstract: Physical exercise can attenuate the effects of aging on the central nervous system by increasing the expression of neurotrophins such as brain-derived neurotrophic factor (BDNF), which promotes dendritic branching and enhances synaptic machinery, through interaction with its receptor TrkB. TrkB receptors are synthesized in the cell body and are transported to the axonal terminals and anchored to plasma membrane, through SLP1, CRMP2 and Rab27B, associated with KIF1B. Retrograde trafficking is made by EDH-4 toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Brain-derived neurotrophic factor has neurobiological and metabolic effects, regulating the survival (Hofer and Barde, 1988), growth (Kalcheim and Gendreau, 1988) and maintenance of neurons (Griesbeck et al, 1995). Its association with physical activity is already known (Almeida et al, 2016; Church et al, 2016); in fact, its expression not only increases after exercise (Park and Kwak, 2017) but also depends on the intensity of exercise (Jeon and Ha, 2017). Previous studies demonstrated that its mRNA and protein expression levels increase in human skeletal muscle after exercise without any release into the circulation (Matthews et al, 2009).…”
Section: Myokines and The Contracting Musclementioning
confidence: 98%
“…Brain-derived neurotrophic factor has neurobiological and metabolic effects, regulating the survival (Hofer and Barde, 1988), growth (Kalcheim and Gendreau, 1988) and maintenance of neurons (Griesbeck et al, 1995). Its association with physical activity is already known (Almeida et al, 2016; Church et al, 2016); in fact, its expression not only increases after exercise (Park and Kwak, 2017) but also depends on the intensity of exercise (Jeon and Ha, 2017). Previous studies demonstrated that its mRNA and protein expression levels increase in human skeletal muscle after exercise without any release into the circulation (Matthews et al, 2009).…”
Section: Myokines and The Contracting Musclementioning
confidence: 98%
“…On the other hand, whereas regular physical activity benefits learning and memory over the whole life course, the benefits are dependent on aspects of physical exercise plans such as speed, time or slope [16][17][18]. For instance, moderate treadmill exercise was shown to positively modulate the concentrations of BDNF and its TrkB receptor in experimental animals [19,20]. Therefore, the different exercise intensities have different effects on learning and memory as well as BDNF/TrkB signaling activities.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced BDNF expression in hippocampal neurons causes a decrease in neurite outgrowth [ 51 ]. MAP2 is a neuron-specific cytoskeletal protein that stabilizes microtubules and is involved in establishing dendritic arborization during development.…”
Section: Discussionmentioning
confidence: 99%